Microwave Synthesis of Some New 1,3-Oxazepine Compounds as Photostabilizing Additives for Pmma Films - Hameed, Ayad (Al-Nahrain Journal of Science, 2018)
The work presented in the current research is concerned with the synthesis of four new compounds containing 1,3-oxazepine and 1,3,4-oxadiazole [1-4] by microwave assisted organic synthesis method through the condensation reaction of 2-[4-(arylidene) phenyl-1,3,4-oxadiazole-5-thiole] with maleic anhydride under variable microwave power (180, 510) watt. The structure of the synthesized compounds was characterized using available spectroscopic methods (H1-NMR, FTIR) and the results obtained are agreement with the proposed structures assigned to these compounds. The photostabilization of poly (methyl methacrylate) PMMA films by of 1,3-Oxazepine compounds [1-4] was investigated. The PMMA films containing concentration of [1-4] 0.5% by weight were produced by the casting method from chloroform solvent. The photostabilization activities of these compounds were determined by monitoring the hydroxyl index with irradiation time. The changes in viscosity average molecular weight of PMMA with irradiation time were also tracked (using benzene as a solvent). The quantum yield of the chain scission (Φcs) of these compounds in PMMA films was evaluated and found to range between 4.2010-5 and 8.7610-5. Results obtained showed that the rate of photostabilization of PMMA in the presence of the additive followed the trend:[1] > [2]> [3]> [4]According to the experimental results obtained, several mechanisms were suggested depending on the structure of the additive. Among them, UV absorption, peroxide decomposer and radical scavenger for photostabilizer mechanisms were suggested